Water conservation in industry - Martins, Márcia Viana Lisboa; Astorga, Oscar Armando Maldonado; Silveira, José Luz (Revista Ciências Exatas, 2008)
The shortage of water supplies, added to the costs of water supplies sources and disposal of effluents in the water basins, according to the law no 9.433/97, has caused the industries to adopt water use management strategies. The water conservation became an indispensable tool in order to reduce the water consume and the effluent generation. This paper presents a procedure of water conservation, which can be applied in several water consumptions industries. The procedure is based on water diagnosis of industry for evaluated the parameters of quality and quantity of the water demand and the effluent generation and will also identify the misuse of water. After water diagnosis it is evaluated ways to more efficient water use. The water system optimization is getting checking the wastewater reuse possibilities and adopt of the processes and/or of the equipment more efficient. The procedure is illustrated with a case study based on red met abattoir industry. The results obtained represent a 10% saving of fresh water.